Analisis Kesadaran Keselamatan Kerja Laboratorium IPA Siswa SMA X di Bone - Nurwadia Sri Putri Rahmadani; Andi Yepita Deviyanti; Hardianty Hardianty; Siti Nurmanis Sari; Cicci Chairunisa Mas'um (Jurnal Siti Rufaidah, 2025)
Laboratory guidelines not only provide students with practical experience but also help them identify hazardous materials and maintain occupational safety in the laboratory. This study aims to determine the level of safety awareness in school laboratories among senior high school students. A survey questionnaire prepared using Google Forms was distributed to 35 twelfth-grade students who were considered to have prior experience in receiving laboratory safety materials. The results of this study indicate that most students have implemented laboratory safety procedures, particularly in the use of basic physical protection. However, the low level of students’ safety awareness in the laboratory is influenced by the limited role of teachers in consistently reminding students of laboratory safety procedures, as well as the lack of clear safety guidelines available in the laboratory. Therefore, it is necessary to strengthen teachers’ involvement and provide comprehensive laboratory safety guidelines so that students can better understand the importance of laboratory safety, especially in the event of accidents